2009
DOI: 10.1109/tit.2009.2023715
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Asymptotically Good Quantum Codes Based on Code Concatenation

Abstract: We explicitly construct an infinite family of asymptotically good concatenated quantum stabilizer codes where the outer code uses CSS-type quantum Reed-Solomon code and the inner code uses a set of special quantum codes. In the field of quantum error-correcting codes, this is the first time that a family of asymptotically good quantum codes is derived from bad codes. Its occurrence supplies a gap in quantum coding theory. As in classical coding theory, we want to construct quantum codes with large minimum dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Work on codes with large k initially focused on random codes, where it was shown that random stabilizers have k, d ∝ n [23][24][25], and more recently that short random circuits generate good codes (meaning that k and d are both proportional to n) [26]. There are also known constructive examples of good stabilizer codes such as those constructed by Ashikhmin, Litsyn, and Tsfasman [27] and others [28][29][30][31]. All of these codes have stabilizer generators with weight ∝ n, however.…”
Section: B Sparse Quantum Codes and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on codes with large k initially focused on random codes, where it was shown that random stabilizers have k, d ∝ n [23][24][25], and more recently that short random circuits generate good codes (meaning that k and d are both proportional to n) [26]. There are also known constructive examples of good stabilizer codes such as those constructed by Ashikhmin, Litsyn, and Tsfasman [27] and others [28][29][30][31]. All of these codes have stabilizer generators with weight ∝ n, however.…”
Section: B Sparse Quantum Codes and Related Workmentioning
confidence: 99%
“…= spackle(K) ∩ G 4 (32b) (30) = spackle(K ∩ ∆) ∪ (spackle(K) ∩ G 2 ) (32c) (31) = spackle(K ∩ ∆) (32d)…”
Section: Proving the Isomorphismmentioning
confidence: 99%
“…The quantum codes obtained in this way are called stabilizer codes. After the establishment of the above connection between quantum codes and classical codes, the construction of stabilizer codes can be converted to that of classical codes with symplectic, Euclidean or Hermitian selforthogonal property (see [1], [7], [15], [16], [21], [25], etc).…”
Section: Introductionmentioning
confidence: 99%
“…Work on codes with large k initially focused on random codes, where it was shown that random stabilizers have k, d ∝ n [16,15,3], and more recently that short random circuits generate good codes [14]. There are also known constructive examples of good stabilizer codes such as those constructed by Ashikhmin, Litsyn, and Tsfasman [2] and others [17,18,34,31]. All of these codes have stabilizer generators with weight ∝ n, however.…”
Section: Sparse Quantum Codes and Related Workmentioning
confidence: 99%